Micromachining Techniques for Millimeterwave Applications: A Short Review - Murad, N.A; Esa, M.; Sabri, M.; A. Rahim, M. K. (ELEKTRIKA- Journal of Electrical Engineering, 2017)
Millimeterwave frequency range gained interest due to the demands on bandwidth and speed in telecommunication system. As the frequency increases, the wavelength is shorter and the devices shrink. To some extent, it is difficult to fabricate the small structure using conventional method. A proper consideration on the manufacturing tolerances is needed in fabricating compact structure precisely as well as minimizing losses and crosstalks between lines in a circuit. Many techniques with different tolerances were discussed. Micromachining is one of the techniques with potential to achieve small structures with great accuracy. This paper presents a short review on micromachining techniques used to manufacture small devices precisely. The techniques discussed are bulk micromachining, LIGA, membrane technology, surface micromachining as well as thick photoresist technique. The process for each technique may differ as well as the tolerances.